2022
DOI: 10.1007/s11356-022-23323-y
|View full text |Cite
|
Sign up to set email alerts
|

A review of water electrolysis–based systems for hydrogen production using hybrid/solar/wind energy systems

Abstract: Hydrogen energy, as clean and efficient energy, is considered significant support for the construction of a sustainable society in the face of global climate change and the looming energy revolution. Hydrogen is one of the most important chemical substances on earth and can be obtained through various techniques using renewable and nonrenewable energy sources. However, the necessity for a gradual transition to renewable energy sources significantly hampers efforts to identify and implement green hydrogen produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(38 citation statements)
references
References 181 publications
0
24
0
Order By: Relevance
“…31 First-order low-pass filtering is performed on the P w-p curve through an FIR filter to filter out high-frequency fluctuations, and a P b curve meeting the expected volatility can be obtained. 32 The calculation formula for the parameters of the battery is as follows 13) where B(0), max[B(t)], and min[B(t)] refer to the initial storage power and maximum and minimum battery capacity, respectively.…”
Section: ■ Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…31 First-order low-pass filtering is performed on the P w-p curve through an FIR filter to filter out high-frequency fluctuations, and a P b curve meeting the expected volatility can be obtained. 32 The calculation formula for the parameters of the battery is as follows 13) where B(0), max[B(t)], and min[B(t)] refer to the initial storage power and maximum and minimum battery capacity, respectively.…”
Section: ■ Methodologymentioning
confidence: 99%
“…The three most common types of electrolyzer for hydrogen production include the PEM electrolyzer, alkaline electrolyzer, and solid oxide electrolyzer . Their advantages and disadvantages are compared in Table S1.…”
Section: Methodsmentioning
confidence: 99%
“…At present, hydrogen production by electrolysis of water using renewable energy power is a low-carbon process with low pollutant emissions. To improve the current situation of “abandoning wind and electricity”, 1 one promising route is to develop the coupling process of hydrogen production and chemical synthesis, which is greatly dependent on the exploration of new efficient electrocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, most countries have depended on energy production from fossil fuels. The exponential increase in the required energy and the adverse environmental effect of fossil fuels drove various nations to use alternative clean energy sources [1]. Hydrogen might be a new fuel for the current age that drives economic advancement and avoids existing fuels' problems.…”
Section: Introductionmentioning
confidence: 99%
“…In case of a surplus of electrical energy produced, it can be sold to reduce the production cost [14]. On the other hand, the hybrid system is mainly used for electricity production, and the excess electricity is used to generate Hydrogen, as stated in [1]. The results showed that Hydrogen production was about 30.4 kg between April and July.…”
Section: Introductionmentioning
confidence: 99%